2021
DOI: 10.2174/1381612827666210224142446
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Epidemiology, Pathology, Diagnosis, Treatment, and Impact

Abstract: : The pandemic, well-known as COVID-19, has been brought about by the coronavirus SARS-CoV-2 and it has distinct characteristics from other coronavirus-related epidemics. This pandemic has been ravaging the whole world for more than a year now and no drugs or vaccines have been found to eliminate this virus from the infected people effectively; only physical measures like social distancing, hand washing and face-mask wearing have been taken to reduce its spreading and very recently Veklury (remdesivir) has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…COVID-19 is caused by the SARS-CoV-2-enveloped virus [1], which became a pandemic in 2020 and is still widespread [2,3]. The COVID-19 infection has the potential to cause multi-organ, systemic complications with a greater risk of thromboembolism [4,5]. As of 2 July 2021, there were more than 182 million confirmed worldwide cases of COVID-19 reported to the WHO, with more than 3 million deaths.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is caused by the SARS-CoV-2-enveloped virus [1], which became a pandemic in 2020 and is still widespread [2,3]. The COVID-19 infection has the potential to cause multi-organ, systemic complications with a greater risk of thromboembolism [4,5]. As of 2 July 2021, there were more than 182 million confirmed worldwide cases of COVID-19 reported to the WHO, with more than 3 million deaths.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 (coronavirus disease 2019), the etiological agent of SARS-CoV-2, is a multisystemic disease classified as a pandemic by the World Health Organization, and it poses a public health problem due to the virus's close-contact transmission and rapid spread [1]. Although mortality rates vary from country to country, mortality is known to be higher for older individuals, and a recent study reported the disease's mortality rate at 36%for patients over 64 years old [2].…”
Section: Introductionmentioning
confidence: 99%
“…The disease caused by SARS-CoV-2, called COVID-19, spread quickly. Before the end of January 2020, there were already reports of contamination in different locations around the world (RAHMAN et al, 2021;SHAHRIAR et al, 2021).…”
Section: Introductionmentioning
confidence: 99%